THE RUSSIAN-UKRAINIAN WAR AS A CATALYST FOR CHANGES IN THE TAXATION OF AGRICULTURAL EXPORTS - Панасюк, Валентина М.; Мужевич, Наталія В.; Трубіцина, Оксана В. (Journal of Strategic Economic Research, 2024)
The Russian-Ukrainian war has significantly impacted the export situation of agricultural products from Ukraine. The "naval blockade" forced the country’s economy to focus on developing alternative transportation routes, such as land grain corridors. Constant changes at the front line, in turn, are reflected in regular changes in current legislation aimed at stabilizing the situation. In wartime conditions, it is extremely important to ensure maximum income for the state budget, which is why the taxation of agricultural exports is under close scrutiny by lawmakers, as this sector accounts for a "lion’s share" of budget revenue. As a result of the study, the specifics of taxing export operations of agricultural products that arose after the introduction of martial law in Ukraine were analyzed. For this, a list of taxes and customs payments that need to be made during export operations was determined. The procedure for registering the supplier as an exporter of products was disclosed. The changes initiated by the Ukrainian Grain Association and adopted at the legislative level in the form of an experimental project were considered, which will allow the verification of subjects in the agro-industrial complex. Exporters can follow two paths: the first is to register in the State Agricultural Register (SAR) if they meet the set criteria; the second is to apply for an exporter’s license through the Ministry of Economy. The issue of currency restrictions that arose with the beginning of martial law was investigated, and changes that may occur in this direction with the implementation of planned bills were assessed. Thus, the article points to the need for attention to the field of taxation of agricultural exports in wartime conditions and constant transformations in the legal environment of foreign economic operations.